A novel Ce–Ta mixed oxide catalyst for the selective catalytic reduction of NOx with NH3 - Zhang, Tao; Qu, Ruiyang; Su, Wenkang; Li, Junhua (Applied catalysis. B, Environmental, 2015)
[Display omitted] •A series of novel CeaTabOx catalysts were firstly prepared by co-precipitation method.•Excellent NH3–SCR activity and N2 selectivity through a relatively wide temperature range.•Ce1Ta1Ox catalyst maintained high NOx conversion in the presence of H2O and SO2.•Ta addition could increase the amount of active sites, oxygen vacancies, and Brønsted acid sites.•The reactivity of surface-adsorbed NH3 and NOx species depended on the temperature. A series of novel CeaTabOx catalysts prepared by a co-precipitation method was investigated on selective catalytic reduction (SCR) of NOx with NH3. It was found that the Ce1Ta1Ox catalyst showed excellent activity, N2 selectivity and strong resistance to H2O and SO2 through a relatively wide temperature range. The CeaTabOx catalysts were characterized using XRD, BET, XPS, H2-TPR, NH3-TPD, NO+O2-TPD and in situ DRIFTS. The characterization results indicated that Ta addition could increase the BET surface area and the surface acidity of the catalysts, lead to the appearance of higher levels of Ce3+ and chemisorbed oxygen species, influence the reducibility of the catalysts, and promote the presence of nitrite and nitrate species. According to the in situ DRIFTS investigations, the reactivity of surface-adsorbed NH3 and NOx species depended on the temperature.